Vertical restraints in an online world: competition authorities gear up their enforcement approach in the digital economy. Issue 1 (March 2019) - Israel, Marc; MacLennan, Jacquelyn; Jeram, Jan
Abstract : The regulation of vertical restraints is a long-standing facet of competition law, governed at the European level by Article 101 TFEU. However, in the new era of digitization, algorithmic price monitoring and price setting has the potential to lead to rapid and widespread price changes across entire online marketplaces for suppliers, often leading to lower prices, which benefit consumers. The manner in which suppliers react to these pressures has resulted in behaviours that may involve collusion, but more often are reminiscent of classic vertical restraints, albeit in the new digital era. The article considers how the European Commission and some Member States' national competition authorities have been tackling vertical restraints in the online world, and considers the implications as the European economy continues to digitize.